Social enrichment during postnatal development induces transgenerational effects on emotional and reproductive behavior in mice - Curley, James P.; Davidson, Stephanie; Bateson, Patrick; Champagne, Frances A. (Frontiers in Behavioral Neuroscience, 2009)
Across species there is evidence that the quality of the early social environment can have a profound impact on neurobiology and behavior. In the present study we explore the effect of communal rearing conditions (three dams with three litters per cage) during the postnatal period on offspring (F1) and grand-offspring (F2) anxiety-like and maternal behavior in Balb/c mice. Females rearing pups in communal nests exhibited increased levels of postpartum maternal care and communal rearing was found to abolish sex-differences in weaning weights. In adulthood, communally reared offspring were observed to display reduced anxiety-like behavior when placed in a novel environment. When rearing their own offspring under standard conditions, communally reared females demonstrated higher levels of motivation to retrieve pups, built higher quality nests, and exhibited higher levels of postpartum care compared to standard reared females. When exposed to an intruder male, communally reared females were more subordinate and less aggressive. F2 offspring of communally reared females were observed to engage in reduced anxiety-like behavior, have larger litter sizes and an increased frequency of nursing on PND 1. Analysis of neuropeptide receptor levels suggest that a communal rearing environment may exert sustained effects on behavior through modification of oxytocin and vasopressin (V1a) receptor densities. Though Balb-C mice are often considered “socially-incompetent” and high in anxiety-like behavior, our findings suggest that through enrichment of the postnatal environment, these behavioral and neuroendocrine deficits may be attenuated both within and across generations.